Implementasi Sistem Pakar Untuk Mendiagnosa Penyakit Pada Perokok Aktif Dan Perokok Pasif Dengan Menggunakan Metode Anfis - Laila Safira; Muhammad Misdram; Dian Ahkam Sani (INTEGER: Journal of Information Technology, 2021)
Abstract. Cigarettes or cigars are cylinders of paper measuring between 70 and 120 mm long and about 10 mm in diameter containing chopped dried tobacco leaves. A person who inhales cigarette smoke is called a smoker. Smokers are divided into active smokers and passive smokers. An active smoker is someone who regularly consumes the smallest amount of cigarettes even though it's only 1 cigarette a day, and a passive smoker is someone who inhales cigarette smoke from an active smoker. Exposure to secondhand smoke can cause serious illness and death. The dangers of smoking on the health of the body have been researched and proven by many people. Lack of self-care, and lack of knowledge about the dangers of smoking make some people no longer think about their health in the future. Many rule out the bad effects caused by cigarette smoke. This is because these effects are not immediately visible when you first smoke. Many smokers are reluctant to get checked out for various reasons. Therefore, researchers made the implementation of an expert system to diagnose diseases in active smokers and passive smokers using the Anfis method. Anfis is an amalgamation of the system's fuzzy interface mechanism described in a neural network architecture. From the results of the implementation trial, the accuracy of the learning rate was 70% - 90% by including the same symptoms.Keywords: Expert System, Cigarettes, Anfis